Virtual network embedding algorithm based on negotiation in distributed environment - Yi-ming JIANG; Ju-long LAN; Dong-nian CHENG; Fang-ming WU (Tongxin xuebao)
The network virtualization is able to offer various customized end-to-end services networks on a shared sub-strate network.However,the existing virtual network embedding algorithms present many problems in reliability and ap-plicability due to their dependence on a centralized manager node.Hence,a virtual network embedding algorithm in dis-tributed environment is proposed,which implements embedding process by the negotiation of several nodes.Moreover,this algorithm makes improvement in reducing communication cost and length of virtual links.Simulation experiments demonstrate that the proposed algorithm can achieve better performance on efficiency of resources utilization and com-munication cost.